2023
DOI: 10.1039/d3nr00205e
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared light-controlled kartogenin delivery of multifunctional Prussian blue nanocomposites for cartilage defect repair

Abstract: Articular cartilage injury repair remains a challenge for clinicians and researchers. Mesenchymal stem cells (MSCs) have multiple differentiation potentials and can be induced to differentiate into the chondrogenic lineage for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In patients with OA, ROS-mediated oxidative stress leads to the differentiation of cartilage into hypertrophic CHOs, resulting in difficulty in forming stable articular cartilage. 85 Toluidine blue staining demonstrated that Fe/ZIF-8/Gel was effective in reducing hypertrophic differentiation of cartilage, exhibiting a morphology essentially identical to that of the sham-operated group after 4 and 8 weeks of treatment (Fig. 6f and Fig.…”
Section: Resultsmentioning
confidence: 82%
“…In patients with OA, ROS-mediated oxidative stress leads to the differentiation of cartilage into hypertrophic CHOs, resulting in difficulty in forming stable articular cartilage. 85 Toluidine blue staining demonstrated that Fe/ZIF-8/Gel was effective in reducing hypertrophic differentiation of cartilage, exhibiting a morphology essentially identical to that of the sham-operated group after 4 and 8 weeks of treatment (Fig. 6f and Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Another study by Yang et al [ 75 ] loaded BMSCs onto gelatin methacryloyl hydrogel microspheres with superwetting properties, enabling sustained release of TGF-β and promoting cartilage regeneration at bone defect sites. By manipulating factors such as carrier material properties, degradation rates, and cross-linking mechanisms, desired release kinetics can be achieved [ 94 , 173 ]. This approach ensures sustained and localized delivery of therapeutic agents, enhancing their biological activity and facilitating targeted cartilage regeneration.…”
Section: Cytokines and Growth Factors In Cartilage Regenerationmentioning
confidence: 99%
“…Graphene oxide, a derivative of graphene with oxygen-containing functional groups, can be bound to hydrogels and has been shown by Liu et al [ 185 ] to promote chondrocytes secretion, reduce joint inflammation, and facilitate AC repair. Another effective approach involves the delivery of kartogenin using multifunctional Prussian blue nanocomposites developed by Liu et al [ 173 ]. This method promotes chondrogenic differentiation while inhibiting excessive MSC differentiation.…”
Section: Tissue Engineering Approaches For Articular Cartilage Regene...mentioning
confidence: 99%
See 1 more Smart Citation